Diagnostic value of cerebrospinal fluid tau, neurofilament, and progranulin in definite frontotemporal lobar degeneration - Joery Goossens; Maria Bjerke; Sara Van Mossevelde; Tobi Van den Bossche; Johan Goeman; Bart De Vil; Anne Sieben; Jean-Jacques Martin; Patrick Cras; Peter Paul De Deyn; Christine Van Broeckhoven; Julie van der Zee; et al. (Alzheimer’s Research & Therapy, 2018)
Abstract Background We explored the diagnostic performance of cerebrospinal fluid (CSF) biomarkers in allowing differentiation between frontotemporal lobar degeneration (FTLD) and Alzheimer’s disease (AD), as well as between FTLD pathological subtypes. Methods CSF levels of routine AD biomarkers (phosphorylated tau (p-tau181), total tau (t-tau), and amyloid-beta (Aβ)1–42) and neurofilament proteins, as well as progranulin levels in both CSF and serum were quantified in definite FTLD (n = 46), clinical AD (n = 45), and cognitively healthy controls (n = 20). FTLD subgroups were defined by genetic carrier status and/or postmortem neuropathological confirmation (FTLD-TDP: n = 34, including FTLD-C9orf72: n = 19 and FTLD-GRN: n = 9; FTLD-tau: n = 10). Results GRN mutation carriers had significantly lower progranulin levels compared to other FTLD patients, AD, and controls. Both t-tau and p-tau181 were normal in FTLD patients, even in FTLD-tau. Aβ1–42 levels were very variable in FTLD. Neurofilament light chain (Nf-L) was significantly higher in FTLD compared with AD and controls. The reference logistic regression model based on the established AD biomarkers could be improved by the inclusion of CSF Nf-L, which was also important for the differentiation between FTLD and controls. Within the FTLD cohort, no significant differences were found between FTLD-TDP and FTLD-tau, but GRN mutation carriers had higher t-tau and Nf-L levels than C9orf72 mutation carriers and FTLD-tau patients. Conclusions There is an added value for Nf-L in the differential diagnosis of FTLD. Progranulin levels in CSF depend on mutation status, and GRN mutation carriers seem to be affected by more severe neurodegeneration.